2009
DOI: 10.1115/1.3106033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laser Pulse Duration and Feed Rate on Pulsed Laser Polishing of Microfabricated Nickel Samples

Abstract: The objective of this work was to improve our understanding of pulsed laser micropolishing (PLμP) by studying the effects of laser pulse length and feed rate (pulses per millimeter) on surface roughness. PLμP experiments were conducted with a multimode neodymium-doped yttrium aluminum garnet (Nd:YAG) laser (1064 nm wavelength) that was focused down to approximately 50 μm diameter and scanned over the stationary workpiece surface. Simulation results presented here and previous work suggest that longer laser pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…Perry et al [1][2][3] have shown that knowledge of the maximum melt duration, t m-max , can be used to determine the minimum critical frequency, f cr , above which there should be a significant reduction in amplitude of the spatial frequency content of a surface and its asperities. The critical frequency is…”
Section: A Fluid Flow Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Perry et al [1][2][3] have shown that knowledge of the maximum melt duration, t m-max , can be used to determine the minimum critical frequency, f cr , above which there should be a significant reduction in amplitude of the spatial frequency content of a surface and its asperities. The critical frequency is…”
Section: A Fluid Flow Modelmentioning
confidence: 99%
“…Perry et al [1][2][3] have modeled PLµP as oscillations of capillary waves with damping resulting from the forces of surface tension and viscosity and a one-dimensional spatial frequency domain analysis was proposed. They have also proposed a critical spatial frequency, f cr , above which a significant reduction in the amplitude of the spatial Fourier components is expected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…51 For example, laser polishing of micro-milled nickel and titanium alloy parts reduced roughness more than 85%. 52 Others 53-55 used pulsed laser micro-polishing (PLμP) to reduce the surface roughness of micro-fabricated and micro-milled parts. A significant range of pulse durations and spot sizes has been effective.…”
Section: Laser Polishing Of Niobium For Srf Accelerator Cavitiesmentioning
confidence: 99%